2017
DOI: 10.1038/sdata.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metagenomic sequencing data of human gut microbiota associated with Blastocystis colonization

Abstract: In the past decade, metagenomics studies have become widespread due to the arrival of second-generation sequencing platforms characterized by low costs, high throughput and short read lengths. Today, although benchtop sequencers are considered to be accurate platforms to deliver data for targeted metagenomics studies, the limiting factor has become the analysis of these data. In a previous paper, we performed an Ion Torrent PGM 16S rDNA gene sequencing of faecal DNAs from 48 Blastocystis-colonized patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the initial study, Blastocystis -colonized patients exhibited a higher abundance of Ruminococcaceae and Prevotellaceae at the family level, whereas Lactobacillaceae, Enterococcaceae, Streptococcaceae and Enterobacteriaceae were enriched in Blastocystis -free patients. Of note, in this initial study, to analyze the Ion Torrent sequencing data, a homemade pipeline was developed using various publicly available tools such as Mothur [13] or EspritTree [29], databases such as the Silva small subunit RNA database and Ribosomal Database Project (RDP) and Perl/Python scripts [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the initial study, Blastocystis -colonized patients exhibited a higher abundance of Ruminococcaceae and Prevotellaceae at the family level, whereas Lactobacillaceae, Enterococcaceae, Streptococcaceae and Enterobacteriaceae were enriched in Blastocystis -free patients. Of note, in this initial study, to analyze the Ion Torrent sequencing data, a homemade pipeline was developed using various publicly available tools such as Mothur [13] or EspritTree [29], databases such as the Silva small subunit RNA database and Ribosomal Database Project (RDP) and Perl/Python scripts [12].…”
Section: Resultsmentioning
confidence: 99%
“…Previously published datasets of a case-control study [12] evaluating the impact of the colonization of the intestinal protozoa Blastocystis sp. on the human gut microbial profile were used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a member of the eukaryome, Tritrichomonas musculis, was shown to activate the epithelial inflammasome and to induce protection against bacterial mucosal infection (Chudnovskiy et al 2016). Other protists, such as Giardia (Barash et al 2017) and possibly Blastocystis (Audebert et al 2016;Siegwald et al 2017), have also been shown to change the resident prokaryotic microbiota. However, data remain conflicting, pointing towards the fact that shifts in the microbiota through given eukaryotes might be strain specific.…”
Section: Eukaryotic Microbiota and The Immune Systemmentioning
confidence: 99%
“…Table 4 reveals that most reads ( >99%) identified from silkworm gut metagenome belong to the domain Bacteria. Taxonomic diversity was analysed not only with shotgun metagenomic data by different tools (BlastP against Nr database and MG-RAST against GenBank), but also by direct 16 S rRNA sequencing 32 , which showed the same tendency ( Table 5 ). Enterococcus , Acinetobacter , Bacillus and Enterobacter are dominant species in both strains ( Fig.…”
Section: Background and Summarymentioning
confidence: 99%